Collapsin Response Mediator Protein 2 (CRMP2) Modulates Mitochondrial Oxidative Metabolism in Knock-In AD Mouse Model - Tatiana Brustovetsky; Rajesh Khanna; Nickolay Brustovetsky (Cells)
We explored how the phosphorylation state of collapsin response mediator protein 2 (CRMP2) influences mitochondrial functions in cultured cortical neurons and cortical synaptic mitochondria isolated from APP-SAA KI mice, a knock-in APP mouse model of Alzheimer’s disease (AD). CRMP2 phosphorylation was increased at Thr 509/514 and Ser 522 in brain cortical lysates and cultured neurons from AD mice. The basal and maximal respiration of AD neurons were decreased. Mitochondria were hyperpolarized and superoxide anion production was increased in neurons from AD mice. In isolated synaptic AD mitochondria, ADP-stimulated and DNP-stimulated respiration were decreased, whereas ADP-induced mitochondrial depolarization was reduced and prolonged. We found that CRMP2 binds to the adenine nucleotide translocase (ANT) in a phosphorylation-dependent manner. The increased CRMP2 phosphorylation in AD mice correlated with CRMP2 dissociation from the ANT and decreased ANT activity in AD mitochondria. On the other hand, recombinant CRMP2 (rCRMP2), added to the ANT-reconstituted proteoliposomes, increased ANT activity. A small molecule (S)-lacosamide ((S)-LCM), which binds to CRMP2 and suppresses CRMP2 phosphorylation by Cdk5 and GSK-3β, prevented CRMP2 hyperphosphorylation, rescued CRMP2 binding to the ANT, improved ANT activity, and restored the mitochondrial membrane potential and respiratory responses to ADP and 2,4-dinitrophenol. Thus, our study highlights an important role for CRMP2 in regulating the mitochondrial oxidative metabolism in AD by modulating the ANT activity in a phosphorylation-dependent manner.